The roles of compliance with Government Procurement Policy: moderating the effects between explanatory factors and Sustainable Public Procurement Practice - Mohd Rezal Jaafar,; Sumaiyah Abd Aziz,; Nathasa Mazna Ramli, (Penerbit Universiti Kebangsaan Malaysia, 2016)
Cases of non-compliance, irregularities and frauds in the government procurement still persist although compliance with Government Procurement Policy (GPP) is mandated by regulations. Complying with procurement standards by law does not necessarily succeeding in implementation of procurement best practices. This paper investigates the moderating impacts of compliance with the GPP on the relationship between the explanatory factors and current Sustainable Public Procurement (SPP) practice in Malaysia, in a comprehensive single framework. Survey questionnaires were administered to 104 government organisations and 177 responses were received from procurement officers. Based on the hierarchical multiple regression analysis, the anticipated outcome of this study is the extent to which the procurement compliance does not guarantee the implementation of SPP practice. The results of this study have provided some explanations regarding the extent of compliance with GPP on the relationship between the explanatory factors and SPP practice.